XVII New Literatures. (21st August 2019) - Batra, Kanika; Griffiths, Michael; Gui, Weihsin; Kamugisha, Aaron; Lorre-Johnston, Christine; Mcneill, Dougal; Niblett, Michael; Raja, Ira; Sharrad, Paul; Uraizee, Joya; Williams, Mark
Abstract: This chapter has seven sections: 1. Africa; 2. Australia; 3. Canada; 4. The Caribbean; 5. South Asia: The Indian Subcontinent and Sri Lanka; 6. New Zealand and Pacific; 7 Southeast Asia. Section 1 is by Kanika Batra, Joya Uraizee, and Mark Williams; section 2 is by Michael Griffiths and Paul Sharrad; section 3 is by Christine Lorre-Johnston and Mark Williams; section 4 is by Michael Niblett and Aaron Kamugisha; section 5 is by Ira Raja; section 6 is by Dougal McNeill; section 7 is by Weihsin Gui.